Optimal fiber mix and prediction model for compressive strength of hybrid fiber reinforced concrete - Ping Gao; Weihong Xie; Yongqiang Ling; Hongfa Xu (PLoS ONE, 2025)
Incorporating single or mixed types of fibers into concrete is an effective method for enhancing its performance. This study aimed to investigate the optimal fiber mix for hybrid fiber reinforced concrete (HFRC) that includes end-hooked steel fibers (ESF), corrugated steel fibers (CSF), and polypropylene fibers (PF), and to predict its compressive strength. To this end, three combinations of HFRC were designed: ESF and CSF (EC-HFRC), ESF and PF (EP-HFRC), and CSF and PF (CP-HFRC), respectively. Plain concrete and single-fiber reinforced concrete with the same mix proportions were also designed for comparison. The compressive strength test results demonstrate slight to moderate enhancement in the concrete’s compressive strength when hybrid fibers are employed. The hybrid effects observed in both EP-HFRC and CP-HFRC are superior to those of EC-HFRC. The optimal fiber mixing combinations are identified as 0.2% PF combined with 1.5% ESF for EP-HFRC and 0.2% PF along with 1.5% CSF for CP-HFRC. Compared with single steel fiber admixture and no fiber admixture, the mixing of hybrid fibers can significantly impact the failure mode of concrete. A novel mathematical model, based on the theory of composite mechanics, has been proposed to accurately predict the compressive strength of single steel fiber reinforced concrete and EC-HFRC, as evidenced by its close alignment with experimental data. The results of this paper provide substantial theoretical support for the design and optimization of HFRC.